STUDY OF THE EDUCATIONAL MANAGEMENT MODEL FOR THE ELDERLY IN THE SPECIAL ECONOMIC DEVELOPMENT ZONE, SOUTHERN BORDER - Boonrat, Arisra; Kaewmano, Chaowanee (Journal of Social Science and Cultural, 2025)
The research aimed to 1) Study the educational management needs of the elderly by gender and age and 2) Study the educational management model for the elderly. The study was conducted using a mixed method by collecting data from the elderly in the Southern Border Special Economic Zone, Songkhla Province in 5 districts (Chana, Thepha, Saba Yoi, Nathawi and Sadao) and collecting data from the elderly aged (60-70 years, 70-79 years and 80 years and over). The sample group was 397 people. The sample size was determined using the Taro Yamane formula with a 95% confidence level and a reliability value of .955. The focus group consisted of 15 people who were purposively selected. The results of the research found that 1) The educational management needs of the elderly in the Southern Border Special Economic Zone, Songkhla Province, classified by gender were at a high level. When considering each aspect, it was found that health and hygiene had the highest needs, followed by social and mental adjustment, and learning. and education management, respectively. The educational management needs of the elderly classified by age found that the elderly with different ages had different educational management needs. 2) The need for educational management formats for the elderly can be summarized as follows: In terms of education management, it emphasizes knowledge that can be applied in daily life or in a career (41.93%). In terms of learning, there should be a budget allocation for agencies specifically related to the elderly (41.14%). In terms of health and hygiene, there should be training courses to prepare for being elderly (37.35%). And in terms of social and mental adjustment, the elderly should receive attention from children and people around them (39.80%).